GREEN SYNTHESIS OF SILVER NANOPARTICLES USING CHITOSAN HYDROLYSATE AS STABILIZING AGENT AND THEIR ANTIBACTERIAL ACTIVITY - Endang Susilowati; Maryani .; Ashadi . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
Silver nanoparticles were successfully synthesized with chitosan hydrolysate as stabilizing agent at room temperature. Silver nitrate, glucose and sodium hydroxide were used as silver precursor, reducing agent and accelerator respectively. Chitosan hydrolysate was produced by enzymatic process with papain enzyme. Molecular weight of chitosan hydrolysate determined by viscosimetry methode based on Mark-Howink equation. The effect of molecular weight of chitosan hydrolysate as stabilizing agent and AgNO3 concentration toward surface plasmon resonance (SPR) of silver nanoparticle was investigated. It is also reported the antibacterial activity of silver-chitosan nanocomposites against Staphylococcus aureus and Escherichia coli. The products of silver nanoparticles were characterized by UV-Vis spectroscopy and transmission electron microscopy (TEM). The result showed that the formation of silver nanoparticles was shown by the appearance of surface plasmon resonance (SPR) at 403–421nm from the corresponding UV-Vis spectra. The molecular weight of chitosan hydrolysate affects the absorbance intensity and the wavelength of SPR. Silver nanoparticles were spherical in shape as identified by TEM images with size in range of 4–26nm. The silver nanoparticles have showed high antibacterial activity against Escherichia coli and Staphylococcus aureus.Key word: green synthesis, silver nanoparticles, chitosan hydrolysate, stabilizing agent, antibacterial activity